1988
DOI: 10.1093/jac/22.supplement_d.155
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and body fluid penetration of fleroxacin in healthy volunteers

Abstract: The pharmacokinetics of fleroxacin after oral administration of 400 mg fleroxacin in twelve healthy volunteers were investigated. All drug analysis was carried out by HPLC. Pharmacokinetic analysis was done by non-compartmental methods. We found that fleroxacin achieves high plasma levels of 5.2 +/- 1.1 mg/l after 1.2 +/- 0.7 h. The high AUC-value of 60.4 +/- 8.4 mg.h/l is the result of complete absorption and the long half-life of 10.8 +/- 1.6 h. The total, renal and non-renal clearance of fleroxacin were 107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…3A to C). It has been hypothesized that two different enzyme systems are involved in the metabolism of fleroxacin (21). DISCUSSION Demethylation is predominantly caused by cytochrome P-450, whereas N oxidation of xenobiotics containing nustudy was undertaken to examine the pharmacokicleophilic nitrogen atoms, as found in fleroxacin, is depen--hanges of fleroxacin, a fluoroquinolone characterized dent on flavoproteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A to C). It has been hypothesized that two different enzyme systems are involved in the metabolism of fleroxacin (21). DISCUSSION Demethylation is predominantly caused by cytochrome P-450, whereas N oxidation of xenobiotics containing nustudy was undertaken to examine the pharmacokicleophilic nitrogen atoms, as found in fleroxacin, is depen--hanges of fleroxacin, a fluoroquinolone characterized dent on flavoproteins.…”
Section: Resultsmentioning
confidence: 99%
“…Fleroxacin is well distributed into interstitial fluid and various tissues (20,21,26,30). Fleroxacin is primarily renally eliminated, with 50 to 60% of the drug being excreted unchanged.…”
mentioning
confidence: 99%
“…Pharmacokinetic studies in humans have demonstrated that fleroxacin is rapidly and completely absorbed from the gastrointestinal tract, achieving a high concentration in the plasma after either oral or intravenous therapy, is metabolized to a minor extent, and has a long elimination half-life, making once-a-day therapy possible (8,21,39,49,51,52,54). Animal studies have suggested that there is excellent penetration of drug into most tissues (5, 18, 30-34, 41, 49, 53), but only limited information on tissue penetration of fleroxacin in humans is available (22,26,41,44,53).…”
mentioning
confidence: 99%
“…It is eliminated primarily by renal clearance, with about 60 to 70% of a dose being recovered unchanged in the urine within 96 h (53-55). These pharmacokinetic properties associated with a wide antibacterial spectrum (5,7,24,35,37,55,56) and a high degree of penetration into body fluids and tissues (12,26,27,36,44,52) allow a once-a-day oral administration. The pharmacokinetic parameters of fleroxacin in healthy young volunteers are well known (33,44,53,54).…”
mentioning
confidence: 99%
“…These pharmacokinetic properties associated with a wide antibacterial spectrum (5,7,24,35,37,55,56) and a high degree of penetration into body fluids and tissues (12,26,27,36,44,52) allow a once-a-day oral administration. The pharmacokinetic parameters of fleroxacin in healthy young volunteers are well known (33,44,53,54). However, serious infections may lead to changes in these parameters through various mechanisms (1,2,4,6,13,28,49,50).…”
mentioning
confidence: 99%